dy/dx = x - yUse substitution:v = x - yDifferentiate with respect to xdv/dx = 1 - dy/dxdy/dx = 1 - dv/dxNow we use above substitutions in differential equationsdy/dx = x - y1 - dv/dx = vdv/dx = 1 - vdv/(1-v) = dxNow integrate both sides:

intg dv/(1-v) = intg dx

-ln (1-v) = x+c

ln(1-v) = -x - c

1 - v = e^(-x-c) = [e^(-x)][e^(-c)]

1 - v = (C)e^(-x) , where C = e^(-Cc)

1 - (x - y) = (C)e^(-x)

y - x + 1 = (C)e^(-x)

y = (C)e^(-x) + x - 1

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now